Pesan Sosial dalam Foto Jurnalistik (Analisis Semiotika dalam Buku Jakarta Estetika Banal , Bab I, III, V, dan VII) - Nuswantara, Jaka Priyo (Jurnal The Messenger, 2014)
This study aims to determine the meaning of denotation and connotation, and social message in the book 'Aesthetics Jakarta Banal', Chapter I, III, V, and VII. The author uses the theory Semiotics of Roland Barthes. Where Semiotics of Roland Barthes uses two stages of analysis denotation and connotation. The research method used is a Roland Barthes semiotic analysis method on the basis that this study analyzes the messages conveyed in the book 'Aesthetics Jakarta Banal', which gives an explanation and overview of issues related to the formulation.  Inferred outline text analysis results indicate that the social life of silence in the city with the concept of light to be seen. Of all the images examined, the object edges and political society into something dominant to be something that should be understood by the reader.